Solve for z 1/12z=-5/6

Math
112z=-56
Multiply both sides of the equation by 12.
12⋅112⋅z=12⋅-56
Simplify both sides of the equation.
Tap for more steps…
Simplify 12⋅112⋅z.
Tap for more steps…
Cancel the common factor of 12.
Tap for more steps…
Cancel the common factor.
12⋅112⋅z=12⋅-56
Rewrite the expression.
1⋅z=12⋅-56
1⋅z=12⋅-56
Multiply z by 1.
z=12⋅-56
z=12⋅-56
Simplify 12⋅-56.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Factor 6 out of 12.
z=6(2)⋅-56
Cancel the common factor.
z=6⋅2⋅-56
Rewrite the expression.
z=2⋅-5
z=2⋅-5
Multiply 2 by -5.
z=-10
z=-10
z=-10
Solve for z 1/12z=-5/6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top